Precision Mold of Prototype Titanium Orthopedic Implant using Metal Injection Molding Approach - Wiranegara, Haruman; Fauzi, Muhammad Nauval; Virdhian, Shinta (Jurnal Rekayasa Mesin, 2020)
MIDC’s researchers in fulfilling Industry Development Programme have taken a step to develop technology in the design application of orthopedic implants to help suppress the rate of imported medical devices in Indonesia. This research objective was to make a prototype plate for a jawbone connector that meets the geometric specifications with the metal injection molding approach. The jawbone connector plate has a very small size of about 2 mm x 20 mm x 0.5 mm that needs precision mold with certain geometric specifications. MIM approach was used, from the literature reviews that show MIM is the appropriate process for manufacturing implants. The phases of MIM were done according to the standard reference which is making raw materials or feedstock, gatting system design, flow simulation, precision mold producing, mold testing, injection process, debinding, sintering, and mechanical product testing. The results of this study were precision molds with several variants and were test using plastic polypropylene to see the performance of the mold. The researchers then produce the jawbone connector implant using feedstock material. The test result conducted in MIDC successfully shows that the mold can produce shapes that match the required geometry.